A Study On Surgical Site Infections Following Lower Segment Caesarean Section At A Tertiary Care Centre - Raman, Amalanshu; Shukla, Bichitra Nath; Rashmi, Rashmi; Raman, Shalini (Journal of Neonatal Surgery, 2025)
Background: Surgical Site Infections (SSIs) remain a leading cause of postoperative morbidity following lower segment cesarean sections (LSCS), especially in low- and middle-income countries. These infections contribute to prolonged hospital stays, increased healthcare costs, and adverse maternal outcomes. Objective: To determine the incidence, risk factors, and demographic correlates of SSIs in patients undergoing LSCS at a tertiary care center over a one-year period. Material and Methods: A prospective observational study was conducted on 400 women undergoing LSCS between April 2024 and April 2025. Postoperative follow-up was done for 7 days. Clinical signs of infection were assessed, and wound cultures were collected when indicated. Data were analyzed using descriptive statistics and chi-square tests to evaluate associations. Results: The incidence of SSI was 8% (32 out of 400 cases). A significant proportion of SSI cases were associated with emergency surgeries, high BMI (≥25), anemia (Hb <11 g/dL), perioperative hyperglycemia (glucose ≥110 mg/dL), and socio-demographic factors such as low socioeconomic status and rural background. Key obstetric risk factors included PROM, PIH, and multiple vaginal examinations. Emergency LSCS accounted for 95% of all SSIs. Conclusion: SSIs following LSCS are predominantly associated with modifiable risk factors, including anemia, hyperglycemia, and emergency procedures. Optimizing preoperative care and stricter aseptic protocols can significantly reduce the SSI burden